An Olefin Metathesis-Based Strategy for the Synthesis of New Antitumoral Compounds Inspired by Natural Products - Cheng-Sánchez, Iván (UMA Editorial, 2019)
his PhD Thesis proposes the discovery and development of new drugs inspired by bioactive natural products, which represent valid platforms for the generation of new chemical entities of pharmaceutical interest. In particular, the selected natural products are (-)-depudecin, solomonamides and celebesides. We have established synthetic strategies oriented to the target, but with the possibility of the extension of such strategies to the construction of a molecular diversity through the generation of analogues. For the synthesis of (-)-depudecin, a unique antitumoral detransforming agent, we have established a new convergent total synthesis utilizing an olefin cross-metathesis (CM) reaction as the key step. In addition, the synthetic route was amenable to stereochemical and functional modifications, allowing the preparation of several analogues, which were used for a structure-activity relationship (SAR) study in order to identify new leads based on depudecin. In the case of the solomonamides, we have developed a synthetic strategy that comprises two phases: a) a cyclisation phase for the construction of the [15]-membered ring contained in these cyclopeptides utilizing an olefin ring-closing metathesis (RCM) as the key reaction; and b) an oxidation phase to give access to the natural products that would allow for the generation of a variety of analogues via oxidative transformations. In addition, we identified several structurally related solomonamide precursors possessing significant cytotoxicities against various tumor cell lines.
In particular, one precursor showed potent antiangiogenic effect in vitro and in vivo, suggesting the potential therapeutic application of solomonamide derivatives as inhibitors of the persistent and deregulated angiogenesis that characterizes cancer. For the last target, the celebesides, [26]-membered cyclodepsipeptides with anti-HIV activity, we envisioned a RCM reaction to access their macrocyclic core. We established a solid-phase synthesis strategy for the preparation of the peptidic chain, while the synthesis of the polyketide fragment was achieved in a stereoselective manner. Fecha de lectura de Tesis Doctoral: 13 de diciembre 2019.
Keywords: Química clínica - Tesis doctorales; Total Synthesis; Natural Products; Olefin Metathesis; Antitumoral; Medicinal Chemistry